Project Management of a Fast Food Network Creating (on the Example of the “Culinary Crossroads” Project) - Zheng, Xiaoyan (Lesya Ukrainka Volyn National University, 2024)
The master's thesis explores and systematizes the methodological and theoretical aspects of project management in the fast-food industry. The first chapter conducts an analysis of the theoretical and methodological foundations of project management in the fast-food sector, including an overview of key concepts, methodological approaches, and project types. The second chapter examines the implementation of the fast-food network establishment project “Culinary Crossroads”, including the formulation of project objectives, strategy, rationale for the choice of fast-food network concept, and project risk analysis. The third chapter discusses the planning and management of the “Culinary Crossroads” project, including the development of project scope, work schedule, team management, budgeting, and financial planning. The analysis and synthesis of the obtained results allow drawing conclusions regarding the peculiarities of managing the fast-food network establishment project and developing recommendations for its further development and improvement. The significance of such projects lies in their impact on the economic and social development of regions. They contribute to job creation, stimulate the local economy by engaging suppliers and producers, and increase the availability of diverse food options for the population. Additionally, the development of a fast food network can enhance service levels and introduce innovative technologies in the public catering sector, positively affecting customer satisfaction and the overall growth of the industry.
Keywords: project management; fast food network; project implementation analysis; project management methodology; project financial planning; project resource management